Development of a solution for adding a collaborative robot to an industrial AGV - aspects related to the collaborative robot and its functions - Costa, João Rafael Arsénio (2019)
Dissertação de Mestrado Integrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia